Improving the reimbursement on delivery cash remittance process of 2GO Express international services pick-up and delivery team through risk mitigation - Velez, Vic Troy (Animo Repository, 2023)
The global pandemic effect of COVID-19 brought severe disruption and spared no single industry to battle reviewing the design and operating effectiveness of its internal controls. In this day and age, the economic uncertainty of the pandemic disrupted business processes and controls, making organizations more susceptible to internal and external fraudulent activities. This action research aimed to address the high number of unremitted reimbursements on delivery and is anchored on establishing strong internal controls, ensuring proper segregation of duties in cash handling, and implementing process standardization to mitigate operational and financial risks and improve process performance, compliance, the efficiency of operations, and process reliability. The application of the combined Enterprise and Risk Management Framework, Plan-Do-Check-Act (PDCA), and Lewin’s Change model serves as our guide that contributed to addressing the causes of the problem. In addition, using three voices and audiences: first, second, and third-person practice facilitated a collaborative co-inquiry and efficient process of improving the cash remittance process. The application of two cycles in this study shows the importance of risk assessment, control activities, and process effectiveness and efficiency in the mitigation of operational and financial risks encompassing any unprecedented events that will happen in the future. The first cycle, which focuses on reducing the high number of unremitted collections, was successfully achieved as we implemented various internal controls. In the second cycle, we focused on addressing the knowledge gaps in systems and approaches, leading to increased operational efficiency and compliance. Hence, the successful results of both cycles are a valid claim that strong internal controls can help mitigate business risks and improve performance, operational efficiency and accountability that drives process excellence in the organization. In essence, this action research can be adapted, enhanced, and used by various organizations within the logistics industry and across all other industries. Keywords: internal controls, risk management process, COSO ERM Framework, standardization, risk mitigation, PDCA, logistics, remittance process, process improvement, change management